Kelayakan Usaha Gula Kelapa Di Kabupaten Kulonprogo - Anisya, Ayu Putri Merry; Wibowo, Teguh Nova Eko (Journal of Agribusiness Science and Rural Development, 2023)
The coconut plant (Cocos nucifera L.) is a strategic commodity that has an important role in the social, cultural and economic aspects of society. Kulon Progo Regency has a coconut plantation area of ​​16,104 ha, with productivity reaching 26,152 tons. Meanwhile, Panjatan District contributed 3,856 tons of coconut production with a coconut plantation area of ​​2,065 ha (BPS Kulon Progo Regency, 2021). The large area and high productivity of coconut in Panjantan District have great potential in developing the coconut sugar agro-industry. Apart from that, coconut sugar business actors in Kulon Progo Regency have received the European standard CSQA (Certified Software Quality Analyst) geographical indication certificate from the Ministry of Law and Human Rights. Coconut sugar has an important role in meeting local sugar needs, especially for people who still rely on natural sugar as a source of sugar. Coconut sugar also has high economic value, is in demand in local and international markets. So, this research wants to see the feasibility of the brown sugar business in Panjatan. The location determination technique was carried out purposively, while sampling was carried out using simple random sampling. Data was collected for one week. The results of the analysis show that the feasibility of the coconut sugar business in Panjatan is worth pursuing, because the results of the R/C value analysis are more than 1, namely 1.02. Capital productivity of 1.93% is greater than the bank savings interest rate of 0.175%. Labor productivity of Rp. 112,729,- exceeds the daily wage in Luweng Lor Village, namely Rp. 40,000,-. The BEP price is Rp. 13,106,- which is smaller than the average price for the coconut sugar household industry in Luweng Lor Village, which is Rp. 13,313,-. Meanwhile, the production BEP of 42 kg is smaller than the average production amount for coconut sugar craftsmen, namely 43 kg. To increase the coconut sugar business by using a larger tool for boiling sap, so that productivity will increase.